DiDaT Weißbuch Verantwortungsvoller Umgang mit digitalen Daten - Orientierungen eines transdisziplinären Prozesses - Scholz, Roland W.; Beckedahl, Markus; Noller, Stephan; Renn, Ortwin (Nomos Verlagsgesellschaft mbH & Co. KG, 2021)
Digitalisation is leading to a fundamental change in all areas of life. This has advantages, but also undesirable side effects. The project "DiDaT - Digital Data as the Subject of a Transdisciplinary Process" deals with unintended side effects or "unseens" of the digital transformation. In this transdisciplinary process, more than 150 experts from science and practice have developed examples for the areas of - mobility, - health, - agriculture, - the future of small and medium-sized enterprises (SMEs) and the - use of social media identified relevant undesirable consequences of the use of digital data and developed socially robust orientations for dealing with them. The results of DiDaT are summarised in this white paper.